Economic and legal regulation of social relations in Ukraine - Луць, Володимир Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The scientific review of a monograph of R. B. Shyshka "Economic and legal regulation of social relations in Ukraine"